Endovascular Therapy for Spontaneous Ilio-Iliac Arteriovenous Fistula Due To Iliac Artery Aneurysm Rupture With Multi-Organ Dysfunction. (August 2020) - Rishi, Muhammad Tipu; Maijub, John; Wang, S. Keisin; Peshkepija, Andi; King, Justin; Gupta, Alok; Fajardo, Andres; Motaganahalli, Raghu L.
Iliac artery aneurysms can rarely present with rupture into adjacent iliac vein resulting in arteriovenous fistula leading to acute cardiac failure or multi-organ failure. End-organ damage can be reversed with timely diagnosis and intervention. Endovascular therapy is an attractive option to treat this pathology besides allowing for a quick recovery and mitigating the risk of mortality associated with open surgical treatment options. We report treatment of this pathology with Endovascular repair with preservation of ipsilateral hypogastric artery flow using an iliac branch graft device. The postoperative course was complicated by type 3 endoleak due to the separation of components between iliac branch graft and aortic stent graft with resultant recurrence of the fistula. Additional endovascular techniques, including placement of a venous stent and stent grafts to bridge the components, was used to treat the endoleak. We present this report due to the unique nature of the recurrent arteriovenous fistula, technical complexity, and resultant multi-organ dysfunction.